Trends in acute pericarditis hospitalizations and outcomes among the elderly in the USA, 1999–2012 - Mody, Purav (Eur Heart J Qual Care Clin Outcomes, 2018)
AIMS: The elderly are at risk of pericarditis from conditions such as malignancy, renal disease, and after cardiac surgery. However, the burden of pericarditis and, especially, the long-term outcomes associated with pericarditis have not been described before among the elderly. METHODS AND RESULTS: We examined hospitalization rates; in-hospital, 30-day, and 1-year all-cause mortality rates; all-cause 30-day readmission rates; length of stay and health care expenditure for Medicare beneficiaries aged 65 years or older with a principal discharge diagnosis of pericarditis from 1999 to 2012. A total of 45 504 hospitalizations were identified. The hospitalization rate for pericarditis remained stable at 26 per 100 000 person-years across the study period and was consistently higher among men and the oldest old. The adjusted all-cause 30-day mortality rates decreased from 7.6% [95% confidence interval (CI) 6.9–8.2] in 1999 to 5.7% (95% CI 4.5–7.1) in 2012 and all-cause 1-year mortality rates decreased from 19.7% (95% CI 18.8–20.8) in 1999 to 17.3% (95% CI 15.3–20) in 2011 respectively. The 30-day all-cause readmission rate remained unchanged at 18% across the study period. The length of stay ranged from a mean of 5.8 days in 1999 to 5.5 days in 2012. The consumer price index adjusted cost per hospitalization increased from $8404 in 1999 to $9982 in 2012. CONCLUSION: The hospitalization rate for acute pericarditis has remained unchanged among older adults. Although mortality rates associated with pericarditis have improved, hospitalization for pericarditis continues to signal a high risk of dying within a year.